Kegagalan Poros Input Gearbox Screw Decanter pada Unit Pengolah Limbah Kelapa Sawit - adi, Adi Febrianton; Sepfitrah; Romiyadi; Yuvendius, Hazra; Irwan, Purnama (JURNAL TEKNIK, 2023)
The use of Centrifuge Decanter as a waste treatment in industry has been widely used. Centrifuge Decanter separates waste in the form of a mixture of solids and liquids (slury) by utilizing the centrifugal force generated by the difference in the rotation of the tube (bowl) and screw conveyor. The rotation of the screw conveyor is reduced through a cycloidal gearbox. The shaft in the cycloid breaks during operation, for that it is necessary to conduct research to determine the cause of this shaft fracture. This research starts from a literature study that discusses the working mechanism of the decanter and the causes of the failure of the cycloidal gearbox shaft. For completeness of the analysis, data collection includes data on engine operation, physical and mechanical properties of the shaft material, fractography of the shaft and the stresses acting on the shaft. From the results of data analysis, it is known that the shaft has ductile fracture due to overload. The load that causes the shaft to break is the torsional load that comes from the rotation of the decanter tube at the initial start of the engine. Torque due to the rotation of the tube produces a shear stress that exceeds the yield stress of the shaft material plus a stress concentration factor in the fractured shaft fillet area.